Wellness needs of academic employees: A case study of a South African university. Issue 3 (4th May 2022) - Jasson, Frances L.; Du Plessis, Marieta; Simons, Abigail
Abstract : Academic employees at Higher Education Institutions face numerous challenges, ranging from workload, student protests, and emergency remote learning. We explored the lived work wellness experiences of South African academics and how well institutional wellness services were meeting these needs. Thirteen academics (eight females; six senior lecturers) completed semi-structured interviews. Thematic analysis identified five themes: (i) need for work-life balance; (ii) wellness services of institutions overlooked academic staff; (iii) work overload among academics; (iv) need for wellness leadership; and (v) the need for responsive wellness initiatives. Although participants acknowledged that they were primarily responsible for their own well-being, responsive wellness initiatives by the institution could support the lived experience of work wellness for academics.